John A. Marston. 2020. Budismo y sociedad en el Sureste de Asia. Ciudad de México: El Colegio de México. 231 pp. ISBN 9786075642185 - García Fernández, Roberto Eduardo (Estudios de Asia y África, 2023)
John A. Marston. 2020. Budismo y sociedad en el Sureste de Asia. Ciudad de México: El Colegio de México. 231 pp. ISBN 9786075642185